An Exploratory Study of Four Urban Community Libraries in Nampula City, Mozambique: Do They Satisfy Community Informational Needs? - Szabo, Elizabeth Eva; Vieira, Ilidia (Libri, 2017)
This exploratory study describes the characteristics of four independent urban community libraries in Nampula city, located in northern Mozambique, East Africa. In a country where public library services are inadequately equipped to address the educational, informational and cultural needs of its citizens, the emergence of urban community libraries in the city indicates that the population is seeking better alternative sources of information. The study profiles four urban libraries to identify their role in the communities they serve and determine whether they conform to Mostert’s (1998) community library model. A case-study design was used with data collection techniques of structured interviews to collect qualitative data from library directors and librarians, a multiple choice questionnaire to obtain user responses, while further statistical data was obtained from collection, circulation and library user records. Findings indicate these four urban libraries only minimally adhere to Mostert’s model and are instead mimicking existing public and school libraries by catering to predominantly secondary and university level students. As a result, the educational, informational and cultural needs of other key groups in the community, such as the illiterate, neo-literate and disadvantaged, are ignored. This is due to a lack of trained library professionals and restrictive library policies.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; access to services / acesso a serviços; education / educação

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

O agronegócio no desenvolvimento do meio rural em Moçambique: perceção e análise das cadeias de valor de milho e da mandioca na província de Nampula - Linha, Paulo (Universidade de Lisboa, 2017)
O Agronegócio em Moçambique poderá ser um factor dinamizador da agricultura, chave para o desevolvimento económico, elemento para a equidade no desenvolvimento social e fundamental para a redução da pobreza e da fome. O estudo analisa as perceções dos atores do agronegócio do milho e da mandioca sobre o impacto destas culturas na vida económica e social no meio rural. Diante desta perspetiva, esta pesquisa teve como objetivo investigar prospectivamente as cadeias de valor das culturas do milho e da mandioca, no corredor de Nacala, com vista a identificar formas de potenciar o desenvolvimento do agronegócio como fator dinamizador da promoção do desenvolvimento socioeconómico sustentável no meio rural. Os resultados alcançados indicam que em Moçambique, de forma geral, o agronegócio do milho e da mandioca é potencial pilar dinamizador que poderá contribuir para o desenvolvimento da agricultura e impulsionar o crescimento económico e o desenvolvimento social se o Estado colocar-se na dianteira na criação, nas zonas de produção, de infraestruturas públicas para a prática de uma agricultura economicamente sustentável e uma legislação flexível e promotora de um clima propício para o agronegócio. Com as infraestruturas públicas criadas nos centros de produção deve-se optar, pelo envolvimento de todos atores do agronegócio num sistema de Integração e Coordenação Vertical, apostando na transformação da baixa renda da agricultura rural em agricultura comercial e competitiva para que efetivamente o agronegócio seja um dos pilares para o combate da fome e da pobreza no meio rural. A Integração e Coordenação Vertical, significa a existência de instituições âncoras que se dedicam a puxar a atividade do agronegócio dos produtores locais na base contratual. Esta forma promete rápida integração ao mercado, crescimento económico, inovação tecnológica, ao mesmo tempo em que protege os direitos e a autonomia do produtor sob regime de integração e coordenação. Agribusiness in Mozambique could be a driving force for agriculture, key to economic development, an element for equity in social development and fundamental to reducing poverty and hunger. The study analyzes the perceptions of corn and cassava agribusiness actors on the impact of these crops on economic and social life in rural areas. The objective of this research was to investigate prospectively the corn and cassava value chains in the Nacala corridor in order to identify ways to promote the development of agribusiness as a driving force for the promotion of sustainable socioeconomic development in the environment rural. The results indicate that, in general, corn and cassava agribusiness in Mozambique are potential pivotal factors that could contribute to the development of agriculture and boost economic growth and social development, if the government takes the initiative to build public infrastructures for an economic sustainable agriculture as well as create a flexible legislation that promotes a proper environment for agribusiness. With the public infrastructures created in the production centers, one must opt for the involvement of all agribusiness actors in a system of Integration and Vertical Coordination, betting on the transformation of low income from rural agriculture into commercial and competitive agriculture so that agribusiness is effectively a pillar to combat hunger and poverty in rural areas. Integration and Vertical Coordination means the existence of anchor institution dedicated to pull the agribusiness activity of the local producers in the contractual basis. This form promises rapid market integration, economic growth, technological innovation, while protecting the rights and autonomy of the producer under integration and coordination.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; agriculture / agricultura; private sector / setor privado